Parallel Robotic Machine Tools - Zhang, Dan.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Research and development of various parallel mechanism applications in engineering is being performed more and more across every industrial field. Parallel robot based machine tools development is considered a key technology of robot applications in manufacturing industries. Parallel Robotic Machine Tools describes the basic theory, approaches, and algorithms in the field. In addition, families of new alternative mechanical architectures, which can be used for machine tools with parallel architecture, are introduced. Also receiving discussion is the design of mechanism systems such as kinematic analysis, stiffness analysis, kinetostatic modeling, and optimization. Author Dan Zhang uses his years of experience in the field to also: Cover the latest material in parallel kinematic machine tools and the junction of parallel robot and machine tools. Include novel conceptions and approaches such as the general kinetostatic model, artificial intelligence based performance optimization, and the global stiffness model. Provide a large numbers of case studies and numerical analyses that will help readers understand and apply the material presented in the book.
Kinematics of Mechanisms -- Architectures of Parallel Robotic Machine -- Planar Parallel Robotic Machine Design -- Spatial Parallel Robotic Machines with Prismatic Actuators -- Spatial Parallel Robotic Machines with Revolute Actuators -- Reconfigurable Parallel Kinematic Machine Tools -- Performance Evaluation of Parallel Robotic Machines -- Design Optimization of Parallel Robotic Machines -- Integrated Environment for Design and Analysis of Parallel Robotic Machine.
Keywords: Engineering; Machinery; Engineering; Control, Robotics, Mechatronics; Manufacturing, Machines, Tools